Tobacco use in first-episode psychosis, a multinational EU-GEI study - Sanchez-Gutierrez, Teresa; Rodriguez-Toscano, E.; Ferraro, Laura; Parellada, Mara; Calvo, Ana; Roldan, Laura; López, G.; Rapado-Castro, Marta; La Barbera, Daniele; La Cascia, Caterina; Tripoli, Giada; Di Forti, Marta; et al. (Psychological Medicine, 2023)
BackgroundTobacco is a highly prevalent substance of abuse in patients with psychosis. Previous studies have reported an association between tobacco use and schizophrenia. The aim of this study was to analyze the relationship between tobacco use and first-episode psychosis (FEP), age at onset of psychosis, and specific diagnosis of psychosis. MethodsThe sample consisted of 1105 FEP patients and 1355 controls from the European Network of National Schizophrenia Networks Studying Gene-Environment Interactions (EU-GEI) study. We assessed substance use with the Tobacco and Alcohol Questionnaire and performed a series of regression analyses using case-control status, age of onset of psychosis, and diagnosis as outcomes and tobacco use and frequency of tobacco use as predictors. Analyses were adjusted for sociodemographic characteristics, alcohol, and cannabis use. ResultsAfter controlling for cannabis use, FEP patients were 2.6 times more likely to use tobacco [p <= 0.001; adjusted odds ratio (AOR) 2.6; 95% confidence interval (CI) [2.1-3.2]] and 1.7 times more likely to smoke 20 or more cigarettes a day (p = 0.003; AOR 1.7; 95% CI [1.2-2.4]) than controls. Tobacco use was associated with an earlier age at psychosis onset (beta = -2.3; p <= 0.001; 95% CI [-3.7 to -0.9]) and was 1.3 times more frequent in FEP patients with a diagnosis of schizophrenia than in other diagnoses of psychosis (AOR 1.3; 95% CI [1.0-1.8]); however, these results were no longer significant after controlling for cannabis use. ConclusionsTobacco and heavy-tobacco use are associated with increased odds of FEP. These findings further support the relevance of tobacco prevention in young populations.
Keywords: age of psychosis onset; heavy use; schizophrenia; smoking; substance use; tobacco; JCR